(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The present study was aimed at a comparative study of the phytoconstituents, antioxidant and antimicrobial properties of four medicinal plants, Ficus capensis, Aristolochia ringens, Albizia zygia and Lannea welwitschii. The leaf of F. capensis and stem bark of A. ringens, A. zygia and L. welwitschii were extracted using methanol. Phytochemical analysis was done spectrophotometrically. Three in vitro antioxidant tests-hydrogen peroxide (H2O2), nitric oxide (NO) and 2, 2-diphenyl-1-picrylhydroxyl (DPPH) scavenging models were employed. Antimicrobial test was done by agar diffusion method against E. coli, Staphylococcus aureus, Klebsiela pneumonia, Bacillus subtilis, Pseudomonas aeruginosa, Salmonella typhi, Candida albicans and Aspergittus spp. Phytochemical analysis revealed that the most abundant phytoconstituents were flavonoids (F. capensis and A. zygia), reducing sugar, terpenoids, alkaloids and tannins. In the antioxidant models, A. zygia was found to produce the least IC50 in two of the models (NO and DPPH). Results of the antimicrobial tests showed that A. zygia showed a broader spectrum of activity than other plants. This study has shown that these plants possess antioxidant and antimicrobial activities which further justify their usage in traditional medicines. A. zygia featured prominently in these activities. Also flavonoids could be responsible for the bioactivities of these plants. Dhaka Univ. J. Pharm. Sci. 16(2): 147-157, 2017 (December)